2021
DOI: 10.2307/j.ctv1b0fvh1
|View full text |Cite
|
Sign up to set email alerts
|

The Global Smartphone

Abstract: Chapter summaries vi List of figures xii List of abbreviations xix List of contributors xx Series Foreword xxii Acknowledgements xxiv 1. Introduction 1 2. What people say about smartphones 27

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Photos from everyday life created feelings of co-presence with small groups of loved ones. The important role of visual material within family and small groups confirms the findings of previous research on relationships at distance (Ahlin, 2018; Miller et al, 2021), which showed that visual communication expresses affection and care and that content often matters less than the act of the communication itself. Similar findings were also presented in Costa’s (2016a) description of social media usage among family members in southeast Turkey who sent photos to each other several times a day whenever they could not see each other face-to-face.…”
Section: Multimodal Scalable Sociality and Polymediasupporting
confidence: 85%
See 1 more Smart Citation
“…Photos from everyday life created feelings of co-presence with small groups of loved ones. The important role of visual material within family and small groups confirms the findings of previous research on relationships at distance (Ahlin, 2018; Miller et al, 2021), which showed that visual communication expresses affection and care and that content often matters less than the act of the communication itself. Similar findings were also presented in Costa’s (2016a) description of social media usage among family members in southeast Turkey who sent photos to each other several times a day whenever they could not see each other face-to-face.…”
Section: Multimodal Scalable Sociality and Polymediasupporting
confidence: 85%
“…This difference might reflect variations in the modes of interaction and socialities, as well as the different impact of the pandemic on people’s life in the two cities. Yet, across the three cities, the increased use of emojis during lockdown reflected a global trend of heightened importance of visual communication to express “care at distance” (Miller et al, 2021; Stark & Crawford, 2015; Walton, 2021). It also demonstrates that emojis facilitated experiences of emotional co-presence and proximity with others at all scales of sociality.…”
Section: Multimodal Scalable Sociality and Polymediamentioning
confidence: 99%
“…By showing how a volunteer organization can creatively but professionally intervene in a humanitarian crisis, I build on existing ethnographic literature that focuses on more lay, street-level solidarity with migrants (e.g., Carney, 2021) and practices of care that rely on the ad-hoc "kindness of strangers" (Smith, 2020) rather than a coordinated organization of skilled laborers. Additionally, this research builds on social science literature on the "global smartphone" as an essential component of contemporary subjectivity (Miller et al, 2021), and particularly on WhatsApp as a "technology of life" in the twenty-first century (Cruz and Harindranath, 2020).…”
Section: Previous Research In Immigrant Mental Healthmentioning
confidence: 99%
“…As the UCL anthropologists recently proposed, the smartphone is now where we live (Miller et al. 2021). As such, digital theology could be branded as “contextual theology” or even as “constructive” theology in its attempt to bring Christian concepts into conversation with digital culture.…”
Section: Digital Theology Is…mentioning
confidence: 99%